Stuart marriage diplomacy : dynastic politics in their European context, 1604-1630 - Caldari, Valentina; Wolfson, Sara J. (Studies in early modern cultural, political and social history, 2018)
Dynastic marriages mattered in early modern Europe. The creation of alliances and the outbreak of wars were tied to continental dynastic politics. This book combines cultural definitions of politics with a wider exploration of institutional, military, diplomatic and economic concerns with a view to providing a more comprehensive understanding of dynastic marriage negotiations. It covers a period from the signing of the Treaty of London in 1604 until after the Anglo-French and Anglo-Spanish peace treaties (1629-30). Stuart Marriage Diplomacy explores how the search for a bride for Princes Henry and Charles started a long process of protracted consultations between the key players of Europe: Spain, Italy, France, Rome, Brussels and the United Provinces. It shows the interconnections between these courts, thus advancing a 'continental turn' in the analysis of Stuart politics in the early seventeenth century, and considers how reason of state was often considered as more crucial than religion or economic concerns in the outcome of the Stuart-Habsburg and Stuart-Bourbon marriage negotiations. It also reveals the extent to which the interactions between Europe and non-European actors in both the Atlantic and the East contributed to a redefinition of European identity. It will engage not only scholars and students of early modern Europe but, more generally, those interested in the history of European courts and royalty.